Ergonomics Risk Awareness in Associated with Employee’s Learning and Experiences - Fazilah, Abdul Aziz; Noraini, Mohd Razali; Nur Najmiyah, Jaafar (2015)
Currently there are many automotive companies still unable to effectively prevent consequences of poor ergonomics in their manufacturing processes. This study purpose is to determine the knowledge and education factors that influence low ergonomics risk awareness among staffs at early product development phase in Malaysia automotive industry. In this study there are three variables, low ergonomic risk awareness, lack of ergonomics knowledge, and insufficient ergonomics education and training. The survey data were gathered from 245 respondents of local automotive companies in Malaysia. The data was analysed through statistical analysis using SPSS software. Study results revealed that low ergonomic risk awareness has influence by lack of ergonomic knowledge and not to insufficient ergonomics education and training. Lack of ergonomic knowledge showed positive linear relationship with the low ergonomic risk awareness. The more lack of ergonomic knowledge; the lower their ergonomic risk awareness. The main contribution of this paper was identified the number of factors of low ergonomics risk awareness and offers better understanding and awareness on ergonomics among employees at early product development phase in automotive manufacturing companies.